“I like everything about it” - Perceived educational value of a digital gaming experience with Assassin’s Creed Odyssey: Discovery Tour - Michele Sardo; Mattia Thibault (Italian Journal of Educational Technology)
While research on videogames in education mostly focuses on demonstrating the effectiveness of Game Based Learning in a broad range of educational contexts, few studies have focused on examining in-depth stakeholders’ perceptions in the educational/teaching area concerning gaming experiences based on a first-person play session. To fill this gap, this study presents the results of a reflexive thematic analysis of the answers to a qualitative survey based on a gaming experience of 13 informants related to the educational field (teachers, researchers, and Master degree students). The game used in the experience was Assassin’s Creed Odyssey: Discovery Tour. The main aim was to understand their perceptions of possible uses of this digital game in formal educational contexts. Our analysis reveals the general perception of a significant overall advantage in the use of this game as an instructional tool compared to a traditional pedagogical approach. Pedagogical solutions for an instructional implementation and design, teaching interventions, critical perspectives are discussed.